The Trust Gap in Online Marketplaces: Policy and Platform Dynamics in the European Union's Digital Economy - Lestari, Putri Ayu (Commercium : Journal of Business and Management, 2024)
This study introduces the Trust Risk Index (TRI) as a novel, policy-relevant metric to capture digital risks privacy, fraud, misinformation, and targeted advertising shaping consumer trust in EU e-commerce. Unlike prior measures, TRI integrates consumer perception and behavior, providing actionable insights for regulators and platforms in restoring trust. The TRI captures consumer concerns related to privacy, fraud, misinformation, and targeted advertising. Using descriptive statistics, regression analysis, and principal component methods, the study analyzes how TRI scores correlate with e commerce engagement across EU countries. Results indicate that higher TRI scores are associated with significantly lower online shopping frequency. Privacy concerns, in particular, emerged as more influential than financial or product related risks. Platforms play a dual role, offering both protective measures and algorithmic risks that affect consumer perception. The findings highlight the importance of regulatory frameworks such as GDPR, the Digital Services Act, and the Digital Markets Act in restoring and maintaining digital trust. The study concludes that addressing non financial digital risks is essential for a sustainable digital economy. The TRI provides a scalable, policy relevant tool for measuring trust deficits and guiding targeted consumer protection strategies in the EU.